Multiply each term in <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn><mi>π</mi></mrow><mrow><mi>b</mi></mrow></mfrac><mo>=</mo><mn>6</mn><mi>π</mi></mstyle></math> by <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Rewrite the equation as <math><mstyle displaystyle="true"><mn>6</mn><mi>π</mi><mi>b</mi><mo>=</mo><mn>2</mn><mi>π</mi></mstyle></math> .

Divide each term in <math><mstyle displaystyle="true"><mn>6</mn><mi>π</mi><mi>b</mi><mo>=</mo><mn>2</mn><mi>π</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>6</mn><mi>π</mi></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>6</mn><mi>π</mi><mi>b</mi></mrow><mrow><mn>6</mn><mi>π</mi></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>π</mi></mstyle></math> .

Cancel the common factor.

Divide <math><mstyle displaystyle="true"><mi>b</mi></mstyle></math> by <math><mstyle displaystyle="true"><mn>1</mn></mstyle></math> .

Simplify <math><mstyle displaystyle="true"><mfrac><mrow><mn>2</mn><mi>π</mi></mrow><mrow><mn>6</mn><mi>π</mi></mrow></mfrac></mstyle></math> .

Cancel the common factor of <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> and <math><mstyle displaystyle="true"><mn>6</mn></mstyle></math> .

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>2</mn><mi>π</mi></mstyle></math> .

Cancel the common factors.

Factor <math><mstyle displaystyle="true"><mn>2</mn></mstyle></math> out of <math><mstyle displaystyle="true"><mn>6</mn><mi>π</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

Cancel the common factor of <math><mstyle displaystyle="true"><mi>π</mi></mstyle></math> .

Cancel the common factor.

Rewrite the expression.

The result can be shown in multiple forms.

Exact Form:

Decimal Form:

Do you know how to Solve for b (2pi)/b=6pi? If not, you can write to our math experts in our application. The best solution for your task you can find above on this page.